2021
DOI: 10.1371/journal.pntd.0009830
|View full text |Cite
|
Sign up to set email alerts
|

Community-based prevalence of rheumatic heart disease in rural Ethiopia: Five-year follow-up

Abstract: Background As little is known about the prevalence and clinical progression of subclinical (latent) rheumatic heart disease (RHD) in sub-Saharan Africa, we report the results of a 5 year follow-up of a community based, echocardiographic study of the disease, originally carried out in a rural area around Jimma, Ethiopia. Methods Individuals with evidence of RHD detected during the baseline study as well as controls and their family members were screened with a short questionnaire together with transthoracic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…The ARGI database deals with late chronic disease and initiatives to diagnose earlier phases of disease including ARF ( 15 , 19 , 20 ) as well as population studies ( 21 ) are essential.…”
Section: Methodsmentioning
confidence: 99%
“…The ARGI database deals with late chronic disease and initiatives to diagnose earlier phases of disease including ARF ( 15 , 19 , 20 ) as well as population studies ( 21 ) are essential.…”
Section: Methodsmentioning
confidence: 99%
“…In a recent community-based prevalence study from south-western Ethiopia, it was reported that the prevalence of RHD was 37.5 per thousand people and this rate is almost 10-fold higher than the prevalence of RHD in schoolchildren from a rural town (Butajira) that was reported nearly 25 years ago. [9][10][11][12] Pediatric data are scarce in Ethiopia regarding complications pertaining to rheumatic heart disease, mortality rate and main cause of death in such patients. Most of the studies are in the adult population and even among them we could not find a study with a special emphasis on RHD patients to point out related complications.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…People living in overcrowded and poor conditions, including in Ethiopia, are at risk of developing this disease. 2,3 The most effective treatment for preventing further infection is benzantine penicillin G (BPG), which is administered via intramuscular injection every month. Alternatively, daily oral penicillin V can be given to a selected number of patients if compliance is guaranteed.…”
Section: Introductionmentioning
confidence: 99%